CSR beyond economy and society: a post-capitalist approach - Roth, Steffen (Journal of business ethics, 2020)
In this article, we draw on established views of CSR dysfunctionalities to show how and why CSR is regularly observed to be both shaped by and supportive of capitalism. We proceed to show that these dysfunctionalities are maintained by both the pro- and anticapitalist approaches to CSR, both of which imply an ill-defined separation of the economy and society as well an overly strong problem or solution focus on political and economic issues. Finally, we present a post-capitalist approach to CSR that overcomes (1) the ill-defined separation of the economy and society, (2) the capitalist bias towards economic rationalities, and (3) the overidentification of society with its political system; this approach thus helps to manage the abovementioned CSR dysfunctionalities.